THE TRANSMUTATION METHOD AND SCHRODINGER EQUATION WITH PERTURBED EXACTLY SOLVABLE POTENTIAL - Koyunbakan, H. (World Scientific Publ Co Pte Ltd, 2009)
In this paper, it is proved the existence of a transmutation operator between two schrodinger equations with perturbed exactly solvable potential. An explicit formula for the solution of nucleus function by using Varsha and Jafari's method is also provided.
Keywords: Transmutation operator; Schrodinger operator; successive approximation method